ANALISIS PENGOLAHAN DATA INTERPRETASI PENGUJIAN PEMBEBANAN HORIZONTAL PADA FONDASI TIANG BOR - Anggarani Budi Ribowo; Syahidus Syuhada; Arif Rahman Hakim Sitepu; Julita Hayati; Satrio Adrian (Yayasan Nusantara Hasana Berdikari, 2025)
One type of load that needs to be taken into account in foundation planning is the lateral load. Lateral load is a force that acts perpendicular to the pile, so it has the potential to cause shifting if the pile does not have sufficient capacity to withstand it. The type of foundation used in this analysis is a bored pile foundation with a diameter of 0.8 m and a pile length of 24 m. The results of the interpretation calculations to obtain the value of the ultimate lateral bearing capacity based on the lateral load test data show differences in the values of each method used. The interpretation calculations that have been carried out obtained the ultimate lateral bearing capacity with the Davisson method of 23,800 tons, with the Chin method obtained a result of 26,455 tons, and the Decourt method of 25,894 tons.